BAMBOO EARRINGS AND BROOCHES MAKING TRAINING WITH METHOD FROM JAPAN - Pramono, Rudy; Juliana, Juliana; Hidayat, July; Darmawan, Cherry; Djakasaputra, Arifin (Universitas Pelita Harapan, 2023)
ABSTRACTBamboo is one of several selected taxonomically related plant categories, extremely rich in species and of great economic and ecological importance. The launching and training activities are expected to be able to develop the domestic market and penetrate the export market, starting from the Asian export market and building brand awareness of Sabatik products, mapping product marketing strategies as well as in positioning, segmenting, targeting markets efficiently and effectively during the product launching period. The activity began with the launching event for Sabatik products as well as training activities for making earrings and brooches followed by visitors or the public who took part in the activities and carried out hands-on practice in making earrings and brooches which was demonstrated by Master Takayuki Shimizu from Japan.The results of the activities carried out received a positive response in which participants stated that the bamboo batik handicrafts were good, cool and interesting and could hold exhibitions more often and maintain activities that could run well and optimally, adding exhibition products so that there were more and providing information on making craft products bamboo.Keyword : training, bamboo earrings, bamboo brooches, Japanese method PELATIHAN PEMBUATAN ANTING DAN BROS BAMBU DENGAN METODE DARI JEPANGABSTRAKBambu merupakan salah satu dari beberapa kategori tanaman terpilih yang terkait secara taksonomi, sangat kaya akan spesies dan sangat penting secara ekonomi dan ekologis. Kegiatan launching dan pelatihan ini diharapkan dapat mengembangkan pasar dalam negeri dan menembus pasar ekspor, dimulai dari pasar ekspor Asia serta membangun kesadaran merek dari produk sabatik, pemetaan strategi pemasaran produk serta dalam positioning, segmenting, targeting pasar yang efisien dan efektif pada masa launching produk. Kegiatan dimulai dengan acara launching produk Sabatik serta kegiatan pelatihan pembuatan anting dan bros diikuti oleh para pengunjung atau masyarakat yang mengikuti kegiatan dan melakukan praktik langsung dalam pembuatan anting dan bros yang didemonstrasikan oleh Master Takayuki Shimizu dari Jepang. Hasil kegiatan yang dilaksanakan mendapatkan respon positif di mana peserta menyatakan hasil kerajinan bambu batik bagus, keren dan menarik serta dapat lebih sering mengadakan acara pameran dan mempertahankan kegiatan yang dapat berlangsung dengan baik dan maksimal, menambahkan produk pameran agar lebih banyak dan memberikan informasi pembuatan produk kriya bambu.